Prevalence of glucose-6-phosphate dehydrogenase deficiency (G6PDd) and clinical implication for safe use of primaquine in malaria-endemic areas of Hainan Province, China - Wen Zeng; Ning Liu; Yuchun Li; Ai Gao; Mengyi Yuan; Rui Ma; Na Jiang; Dingwei Sun; Guangze Wang; Xinyu Feng; Xinyu Feng (Frontiers Media S.A., 2022)
Primaquine, the only licensed antimalarial drug for eradication of Plasmodium vivax and Plasmodium ovale malaria, may cause acute hemolytic anemia in individuals with glucose-6-phosphate dehydrogenase deficiency (G6PDd) during treatment. The different prevalence and distribution patterns of G6PDd in Hainan, the ancient malaria-endemic area, are unclear. This study included 5,622 suspected malaria patients between 2009 and 2011 in 11 counties of Hainan. Glucose-6-phosphate dehydrogenase deficiency prevalence was determined using the fluorescent spot test (FST) and malaria patients was confirmed by a positive light microscopy. The G6PDd prevalence for different ethnic groups, genders, and counties were calculated and compared using χ2-test. Spatial cluster and Spearman rank correlation of G6PDd prevalence and malaria incidence were analyzed. The overall G6PDd prevalence of study population was 7.45%. The G6PDd prevalence of males, Li ethnic minority, and malaria patients was significantly higher than that of females, Han ethnic majority, and non-malarial patients (p < 0.01), respectively. The spatial cluster of G6PDd and malaria located in south-western and central-southern Hainan, respectively, with no significant correlation. The study provides essential information on G6PDd prevalence in ancient malaria-endemic areas of Hainan Province. We also highlight the need for a better understanding of the mechanisms underlying the relationship between G6PDd prevalence and malaria incidence. These findings provide a reference for the safety of the primaquine-based intervention, even after malaria elimination.